2012
DOI: 10.1080/00028487.2012.667044
|View full text |Cite
|
Sign up to set email alerts
|

Precision and Accuracy of Estimators of the Proportion of Hatchery‐Origin Spawners

Abstract: For salmon populations in the Columbia River basin, many of which are listed under the U.S. Endangered Species Act of 1973, reliable estimation of the proportion of hatchery‐origin spawners in spawning areas (p) is needed to make inferences about their status and potential for interbreeding with wild‐origin adults, which may reduce the genetic fitness of subsequent generations. Despite its importance, accurate and precise techniques for estimating p are lacking, especially when there are spawner inputs from mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 17 publications
(17 reference statements)
0
10
0
Order By: Relevance
“…Currently, several published approaches for estimating p, including Bayesian (e.g., Geiger 1994; Barber et al 2011) or frequentist (e.g., Hankin 1982;Hinrichsen et al 2012) methods of estimation are based on tagging or marking (CWTs, otolith marks, or adipose fin clips) of juveniles prior to release. Dauer et al (2009) proposed a modified mark-recapture method for iteroparous steelhead Oncorhynchus mykiss based on spawn checks (reabsorption of scales during previous freshwater migration due to high energy demands of egg or milt production, which Rideout et al (2005) identified in upriver migrating adults).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Currently, several published approaches for estimating p, including Bayesian (e.g., Geiger 1994; Barber et al 2011) or frequentist (e.g., Hankin 1982;Hinrichsen et al 2012) methods of estimation are based on tagging or marking (CWTs, otolith marks, or adipose fin clips) of juveniles prior to release. Dauer et al (2009) proposed a modified mark-recapture method for iteroparous steelhead Oncorhynchus mykiss based on spawn checks (reabsorption of scales during previous freshwater migration due to high energy demands of egg or milt production, which Rideout et al (2005) identified in upriver migrating adults).…”
mentioning
confidence: 99%
“…Dauer et al (2009) proposed a modified mark-recapture method for iteroparous steelhead Oncorhynchus mykiss based on spawn checks (reabsorption of scales during previous freshwater migration due to high energy demands of egg or milt production, which Rideout et al (2005) identified in upriver migrating adults). However, the method of Hinrichsen et al (2012), which was originally applied to CWT and VM data, is the only published approach that produces release-specific estimators of p and their standard errors when there are multiple hatchery releases contributing fish to the spawning grounds. In the Columbia River basin, fish originating from different source hatcheries are known to stray into the same spawning area (McClure et al 2008;Hinrichsen et al 2012).…”
mentioning
confidence: 99%
See 3 more Smart Citations